2014
DOI: 10.1002/wcc.294
|View full text |Cite
|
Sign up to set email alerts
|

Investigating El Niño‐Southern Oscillation and society relationships

Abstract: Throughout at least the past several centuries, El Niño-Southern Oscillation (ENSO) has played a significant role in human response to climate. Over time, increased attention on ENSO has led to a better understanding of both the physical mechanisms, and the environmental and societal consequences of the phenomenon. The prospects for seasonal climate forecasting emerged from ENSO studies, and were first pursued in ENSO studies. In this paper, we review ENSO's impact on society, specifically with regard to agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 118 publications
0
42
0
6
Order By: Relevance
“…The contributions of natural climatic causes to the total P variance in the inter-annual, decadal and trend components were estimated in 84 %, 14 % and 2 % in Central America respectively (Hidalgo León et al 2015). Understanding climate variability through time is key as adapting to climate variability is a great step forward in the adaptation to climate change (Zebiak et al 2014). Climate variability in the form of El Niño-Southern Oscillation (ENSO), for example, impacts many society's aspects such as agriculture and food security, water resources, health, disaster occurrences, and numerous other means (Zebiak et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions of natural climatic causes to the total P variance in the inter-annual, decadal and trend components were estimated in 84 %, 14 % and 2 % in Central America respectively (Hidalgo León et al 2015). Understanding climate variability through time is key as adapting to climate variability is a great step forward in the adaptation to climate change (Zebiak et al 2014). Climate variability in the form of El Niño-Southern Oscillation (ENSO), for example, impacts many society's aspects such as agriculture and food security, water resources, health, disaster occurrences, and numerous other means (Zebiak et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding climate variability through time is key as adapting to climate variability is a great step forward in the adaptation to climate change (Zebiak et al 2014). Climate variability in the form of El Niño-Southern Oscillation (ENSO), for example, impacts many society's aspects such as agriculture and food security, water resources, health, disaster occurrences, and numerous other means (Zebiak et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its great influence around the globe, early prediction of strong El Niño and La Niña events can be of great value to take measures to reduce damage (Zebiak et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some research findings have indicated the usefulness of weather forecasts for reducing vulnerability of rain-fed agriculture to drought, flooding and extremely low or high temperature [22][23][24][25][26]. Initiatives to promote access of African farmers to weather forecasts include formation of several regional Climate Outlook Forums (COFs) in the late 1990s [27][28][29][30]. Similarly, growing need of weather forecasts has triggered establishment of Global Framework for Climate Services [31] by the World Meteorological Organization (WMO).…”
Section: Introductionmentioning
confidence: 99%